2020
DOI: 10.1002/ccd.28705
|View full text |Cite
|
Sign up to set email alerts
|

Two‐year follow‐up of a randomized multicenter study comparing a drug‐coated balloon with a drug‐eluting stent in native small coronary vessels: The RESTORE Small Vessel Disease China trial

Abstract: Objectives To report the clinical outcomes of the RESTORE drug‐coated balloon (DCB; Cardionovum, Bonn, Germany) for treatment of de novo small vessel disease (SVD) beyond 1 year. Background Previous reports have demonstrated the noninferiority of the RESTORE DCB to the RESOLUTE Integrity drug‐eluting stent (DES; Medtronic, Minneapolis, Minnesota) in terms of 9‐month in‐segment percent diameter stenosis. Methods In the prospective, multicenter, noninferiority RESTORE SVD China trial, 230 patients with visually‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 30 publications
(36 reference statements)
3
13
0
Order By: Relevance
“…Also, the RESTORE SVD randomized trial compared DCB with zotarolimus-eluting stent in 256 patients with de novo lesions within vessels between 2.0 and 2.75 mm in size [66]. Target lesion failure did not differ significantly between DCB and DES group at two years (5.2% vs. 3.7%, p = 0.75) [66].…”
Section: Drug-coated Balloonsmentioning
confidence: 99%
“…Also, the RESTORE SVD randomized trial compared DCB with zotarolimus-eluting stent in 256 patients with de novo lesions within vessels between 2.0 and 2.75 mm in size [66]. Target lesion failure did not differ significantly between DCB and DES group at two years (5.2% vs. 3.7%, p = 0.75) [66].…”
Section: Drug-coated Balloonsmentioning
confidence: 99%
“…This was shown in a study that demonstrated an increased incidence of stent thrombosis among AMI patients treated with DES as compared with balloon angioplasty alone, thus paving a potential role of a DCB in PPCI [5]. The presence of a drug on the semi-compliant DCB provides a potential advantage in reducing the potential risk of in-stent restenosis or stent thrombosis [12].…”
Section: Discussionmentioning
confidence: 98%
“…At 9 months, similar in-segment percent diameter stenosis was found (29.6 ± 2% versus 24.1 ± 2%, p < 0.001 for non-inferiority) and there was no difference in TLR, cardiac death, MI and any revascularization. No difference was also found in TLF (4.4% versus 2.6%, p = 0.72) after 1 year and up to 2 years (5.2 versus 3.7%, p = 0.75) [ 36 ].…”
Section: Methodsmentioning
confidence: 99%